2005
DOI: 10.1074/jbc.m504699200
|View full text |Cite
|
Sign up to set email alerts
|

Diverse Biochemical Properties of Shp2 Mutants

Abstract: Mutations in the Src homology 2 (SH2)-containing protein-tyrosine phosphatase Shp2 (PTPN11) underlie half of the cases of the autosomal dominant genetic disorder Noonan syndrome, and somatic Shp2 mutations are found in several hematologic and solid malignancies. Earlier studies of small numbers of mutants suggested that disease-associated mutations cause constitutive (SH2 binding-independent) activation and that cancer-associated mutants are more active than those associated with Noonan syndrome. We have chara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

29
320
2
2

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 261 publications
(353 citation statements)
references
References 49 publications
29
320
2
2
Order By: Relevance
“…As additional controls, we verified that the well-characterized catalytically dead C459G construct displayed no PTP activity, and that the leukemia-associated D61Y mutant and of the NS-associated D61del mutant have an increased PTP activity compared to WT-SHP-2. These two mutants are not significantly overstimulated by the IRS1-pY1172 peptide in these conditions, but this is in agreement with a previous report [8]. In addition, when the immunocomplexes were incubated with the activating peptide alone, the release of phosphate was undetectable for any of SHP-2 construct (data not shown), indicating that this phosphopeptide was not significantly dephosphorylated by SHP-2 when used in these conditions appropriate to observe its activating effect.…”
Section: Ptp Activity Of Ls Mutants Is Abolished When Assayed Usingsupporting
confidence: 92%
See 1 more Smart Citation
“…As additional controls, we verified that the well-characterized catalytically dead C459G construct displayed no PTP activity, and that the leukemia-associated D61Y mutant and of the NS-associated D61del mutant have an increased PTP activity compared to WT-SHP-2. These two mutants are not significantly overstimulated by the IRS1-pY1172 peptide in these conditions, but this is in agreement with a previous report [8]. In addition, when the immunocomplexes were incubated with the activating peptide alone, the release of phosphate was undetectable for any of SHP-2 construct (data not shown), indicating that this phosphopeptide was not significantly dephosphorylated by SHP-2 when used in these conditions appropriate to observe its activating effect.…”
Section: Ptp Activity Of Ls Mutants Is Abolished When Assayed Usingsupporting
confidence: 92%
“…Following immunoprecipitation, the PTP activity of the different constructs was assayed using as substrate a synthetic phosphopeptide encompassing Y529 of Src, a standard in vitro substrate of PTP [3,9]. To test these mutants under stimulation by an upstream SHP-2 activator, the immunocomplexes were also incubated with 10 lM of a phosphopeptide containing the SHP-2-binding site of IRS-1 (IRS1-pY1172) [8]. As shown in Fig.…”
Section: Ptp Activity Of Ls Mutants Is Abolished When Assayed Usingmentioning
confidence: 99%
“…The results of the substrate-trapping experiment revealed that DM/T507K SHP-2-Myc specifically coprecipitated several tyrosinephosphorylated proteins with molecular masses of approximately 65 000B70 000 Da, which were not coprecipitated with DM SHP-2-Myc or DM/E76K SHP-2-Myc ( Figure 3b, lanes 5-7). We also note that the substrate specificity of DM/E76K SHP-2-Myc did not differ from that of DM SHP-2-Myc, indicating that E76K is a hypermorphic but not neomorphic SHP-2 mutation as has been suggested (Keilhack et al, 2005) ( Figure 3b). From these results, we concluded that T507K SHP-2 exhibits altered substrate specificity either through acquisition of new substrates or significant alterations in its interaction with particular substrates.…”
Section: Resultssupporting
confidence: 69%
“…In this phosphatase assay, the E76K mutant of SHP-2, the most common leukemia-specific mutant that causes complete relief of autoinhibition and full activation (Neel et al, 2003;Keilhack et al, 2005;Tartaglia et al, 2006), exhibited more than 100-fold activity of wild-type SHP-2. In contrast, the T507K mutant showed only twofold increase in phosphatase activity compared with that of wild-type SHP-2 ( Figure 2b).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation